Cryopreservation of hematopoietic stem and progenitor cells amplified ex vivo from cord blood CD34+ cells. Issue 9 (11th December 2012) - Duchez, Pascale; Chevaleyre, Jean; Brunet de la Grange, Philippe; Vlaski, Marija; Boiron, Jean‐Michel; Wouters, Guy; Ivanovic, Zoran
<x xml:space="preserve">Abstract</x> Background Our ex vivo expansion procedure starting from cord blood (CB) CD34+ cells enabled expansion of committed progenitors (CPs) without a negative impact on hematopoietic stem cells (HSCs) exhibiting both short‐ and long‐term repopulating capacity. Upgraded to clinical scale (Macopharma HP01 in the presence of stem cell factor, FLT3‐L [100 ng/mL each], granulocyte–colony‐stimulating factor [10 ng/mL], and thrombopoietin [20 ng/mL]), it is being used for an ongoing clinical trial (adult allogeneic context) yielding promising preliminary results. Transplantation of ex vivo expanded CB cells is becoming a reality, while the issue of expanded cells' cryopreservation emerges as an option that allows the conservation of the product for transportation and future use. Here, we investigated whether it is possible to maintain the functional HSC and CP properties after freezing and thawing of expanded cells. Study Design and Methods We compared cryopreservation efficiency of the ex vivo expanded CB cells using the standard protocol (freezing solution human serum albumin (HSA)‐dimethyl sulfoxide [DMSO]) with the newly designed protocol based on an enriched freezing solution (HP01‐DMSO) with respect to the viability index, number of CD34+ and total cells, and recovery of CPs (colony‐forming units) and HSCs (NOG/Scid/gamma–null mice engraftment). Results Cryopreservation and thawing of expanded CB cells using the "standard" procedure (HSA‐DMSO) reduced recovery of the CPs (40%) and HSCs (drastically decreasing engraftment capacity). HP01‐based protocol resulted in improvement of preservation of both CPs (>60%) and HSCs (nonaltered engraftment capacities). Conclusion Functional maintenance of the expanded graft by cryopreservation is feasible in conditions compatible with human cell therapy requirements.